Van der Waals superlattices. Issue 5 (2nd September 2021) - Ren, Huaying; Wan, Zhong; Duan, Xiangfeng
Abstract : This perspective explores the development of van der Waals superlattices, which are manipulated and constructed at atomic thick level, and points out potential applications and possible future directions of this new class of materials.